A Solid‐Solution Approach to Mixed‐Metal Metal–Organic Frameworks – Detailed Characterization of Local Structures, Defects and Breathing Behaviour of Al/V Frameworks. Issue 26 (27th June 2013) - Kozachuk, Olesia; Meilikhov, Mikhail; Yusenko, Kirill; Schneemann, Andreas; Jee, Bettina; Kuttatheyil, Anusree V.; Bertmer, Marko; Sternemann, Christian; Pöppl, Andreas; Fischer, Roland A.
Abstract: The doping of [Al(OH)L] n [L = 1, 4‐benzenedicarboxylate (bdc) or 1, 4‐naphthalenedicarboxylate (ndc)] with vanadium ions yields crystalline porous mixed‐metal solid‐solution metal–organic frameworks (MOFs) of general formula [(AlOH)1– x (VO) x L] n ( x can be varied in the whole range from 0 to 1). Several characterization methods, including powder X‐ray diffraction (PXRD), electron paramagnetic resonance (EPR), solid‐state NMR and FTIR spectroscopy, strongly support the effective incorporation of vanadium cations. The Al/V‐doped MOFs are isostructural to the parent monometallic MOFs and show a characteristic uniform dependence of the cell parameters on the metal ratios. Detailed spectroscopic investigation provided evidence that the introduced species are fairly well ordered. Interestingly, for low amounts of doped vanadium for both activated and as‐synthesized Al/V phases, the EPR results revealed the presence of vanadyl units as local defects in pseudo‐octahedral or square‐pyramidal environments, which are different from those in the parent MIL‐47(V). This observation matches the nonlinear response of the adsorption properties on variation of the composition. Remarkably, the presence of such mixed Al/V chains strongly affects the breathing behaviour of the materials. Both CO2 sorption and in situ PXRD studies validated a gradual change from highly flexible (with easily induced phase transitions) to totally rigid structures upon increasing vanadium content. Abstract : Systematic studies on the doping of [Al(OH)L] n [L = 1, 4‐benzenedicarboxylate (bdc) or 1, 4‐naphthalenedicarboxylate (ndc)] metal–organic frameworks (MOFs) with V ions to obtain [(AlOH)1– x (VO) x L] n (0 < x < 1) solid‐solution materials are reported. Detailed characterization allowed us to examine the correlations between compositions and the structures and properties of the final mixed‐metal materials.